2010
DOI: 10.1111/j.1574-6941.2010.00905.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the gene trzN and biogeographic patterns among atrazine-degrading bacteria isolated from 13 Colombian agricultural soils

Abstract: The following study evaluated the diversity and biogeography of 83 new atrazine-degrading bacteria and the composition of their atrazine degradation genes. These strains were isolated from 13 agricultural soils and grouped according to rep-PCR genomic fingerprinting into 11 major clusters, which showed biogeographic patterns. Three clusters (54 strains) belonged to the genus Arthrobacter, seven clusters (28 strains) were similar to the genus Nocardioides and only one strain was a gram-negative from the genus A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…It is noteworthy that in all the microcosms where genotype atzA/atzB was added, also the trzN gene was observed. The prevalence of trzN over atzA gene in the soil environment reported by Arbeli and Fuentes (2010) might explain why it was often encountered in our experiment. Overall, the measured degradation gene numbers were high in bioaugmented treatments, but often below detection limit in the biostimulated treatments.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…It is noteworthy that in all the microcosms where genotype atzA/atzB was added, also the trzN gene was observed. The prevalence of trzN over atzA gene in the soil environment reported by Arbeli and Fuentes (2010) might explain why it was often encountered in our experiment. Overall, the measured degradation gene numbers were high in bioaugmented treatments, but often below detection limit in the biostimulated treatments.…”
Section: Discussionmentioning
confidence: 53%
“…The latter route is well described and catalyzed by the enzymes encoded by the atzABCDEF genes (de Souza et al, 1996). Instead of atzA, the functional homolog, trzN gene (Mulbry et al 2002), may be more commonly observed in the environment (Arbeli and Fuentes 2010). An alternative atrazine degradation pathway, initiated by a dealkylation reaction, is carried out by a P-450 cytochrome system in certain strains of Rhodococcus species (Nagy et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…C190 was the first Grampositive atrazine degrading bacterium isolated from a Canadian agricultural soil frequently exposed to this herbicide (Topp . Subsequently, other Gram-positive atrazine degraders have been characterized, belonging to Nocardioides (Piutti et al 2003;Yamazaki et al 2008) or the Arthrobacter genus (Strong et al 2002;Devers et al 2007;Arbeli and Fuentes 2010). Most of these strains harbor a trzN-atzBC gene combination allowing the transformation of atrazine to cyanuric acid (Sajjaphan et al 2004;Udiković-Kolić et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these strains harbor a trzN-atzBC gene combination allowing the transformation of atrazine to cyanuric acid (Sajjaphan et al 2004;Udiković-Kolić et al 2012). Several strains harbor a more complete gene combination of trzN-atzCDEF (Arbeli and Fuentes 2010) or trzNatzBC-trzD (Vaishampayan et al 2007) allowing the complete mineralization of atrazine to simple compounds naturally present in the environment. Likewise, our isolate has the trzNatzBC gene combination responsible for the transformation of atrazine to cyanuric acid.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports on atrazine mineralization by wide varieties of bacteria such as Pseudomonas, Acinetobacter, Agrobacterium, Rhodococcus and Arthrobacter (Vibber et al, 2007;Li et al, 2008;Siripattanakul et al, 2009;Arbeli &Fuentes, 2010 andEl Sebai et al, 2012). The capability of microorganisms to utilize atrazine as a carbon, energy and/or nitrogen source was clearly demonstrated (Struthers et al, 1998;Rousseaux et al, 2001 andDevers et al, 2007).…”
Section: Introductionmentioning
confidence: 99%